Pesan Moral dalam Film The Sheerk (2001) - Fahlepi, Gabriel Mohammad Alfarez (Calakan : Jurnal Sastra, Bahasa, dan Budaya, 2025)
Childhood is an important phase in the formation of a person's personality and character. At this time, children begin to absorb moral and ethical values that will shape their way of thinking, attitudes and behavior in the future. This research aims to analyze the moral message contained in the film The Shrek (2001). This research uses a qualitative approach with descriptive methods. Data collection techniques were carried out using descriptive qualitative methods. The focus of this research is to identify moral messages for oneself and others. The results of the analysis show that the film The Shrek (2001) contains various moral messages, such as accept and love who you are, appearance is not everything, Don’t be scared to show your feeling, don’t judge someone from their appearance, Love will accept who you really are, friendship can come from anywhere and any background. These messages are conveyed through key scenes and dialogue that reflect strong moral values. This film provides important lessons for children in understanding the values of life and strengthens the function of children's literature as an educational and inspiring learning medium.